Work-family conflict, stress, and satisfaction among married female public Elementary teachers. - Arsenio, John Clint C.
This is a descriptive and correlational study which sought to explore the relationship of work-family conflict, stress and satisfaction among the respondents . Sixty-two (62) married female public elementary teachers participated in the study. Survey questionnaires were given to gather data about the studied variables., Results of the study showed that respondents are generally experiencing high level of work-family conflict and work-related stress but with low level of family-related stress. In general, respondents have positive attitude towards their job, experience less marital distress and have high level of life satisfaction. Relationships between these studied variables were also examined.